Development of the ex vivo laryngeal model of phonation. (3rd February 2015) - Howard, N. Scott; Mendelsohn, Abie H.; Berke, Gerald S.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The direct study of human phonation is limited by the invasive and painful nature of human laryngeal neuromuscular manipulation. As a platform for the study of human phonation, indirect models have been utilized for decades such as animal, cadaveric, and computational. We sought to develop a research method allowing direct scientific control of virtually living larynges to expand our ability to understand human phonation. Study Design Canine and porcine models. Methods Nineteen canine larynges were surgically removed and reperfused with progressively adapting methodologies to create ex vivo phonation. Results Full neuromuscular stimulation and phonation were ultimately achieved in the ex vivo larynx. As compared with alternative perfusate solutions, heparinized whole blood was found to result in the most robust neuromuscular response. Modification of the reperfusion technique from a continuous flow to a pulsatile pump system resulted in dramatic increases in neuromuscular response and longevity of the organ. The experimental findings were repeated to demonstrate reliability of the ex vivo model. Conclusions The ex vivo larynx model is demonstrated to be a repeatable platform for phonatory research. The process of development has been comprehensively described in the present report. Although the described experimental model was designed for phonatory research, this model can be readily adapted for investigations of organ transplant preservation techniques, effects of organ ischemia, and neuromuscular reinnervation capabilities. Level of Evidence NA Laryngoscope, 125:1414–1419, 2015